PR And Consumer Behavior: Economic Implications for Strategic Marketing in Competitive Markets - Lihui Zhang (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Public Relations (PR) plays a pivotal role in shaping consumer behavior and driving economic outcomes in competitive markets. This study examines the economic implications of PR strategies on consumer decision-making processes, focusing on the interplay between PR activities, consumer perceptions, and purchasing behavior. Using a mixed-methods approach, the research combines quantitative surveys with 500 participants and qualitative interviews with 20 marketing professionals to assess the effectiveness of PR campaigns. Statistical analyses, including regression models, ANOVA, and factor analysis, reveal that PR significantly impacts brand loyalty, consumer trust, and purchase intentions. Media relations emerged as the most effective PR activity, while CSR initiatives and event sponsorships also demonstrated notable influence. Demographic variations were observed, with younger consumers responding more positively to media relations and older consumers prioritizing CSR initiatives. Income-based differences further highlighted the importance of tailoring PR strategies to specific consumer segments. The findings underscore the importance of integrating PR into strategic marketing frameworks to enhance market competitiveness and achieve long-term economic benefits. This study contributes to the growing body of literature on the economic implications of PR and offers practical recommendations for businesses seeking to leverage PR for strategic advantage in competitive markets.